1998
DOI: 10.1016/s0895-7061(97)00319-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Metabolic Effects of Transdermal Clonidine in Patients With Hypertension and Non–Insulin-Dependent Diabetes Mellitus

Abstract: The aim of this study was to evaluate the effect of transdermal clonidine on hemodynamic and metabolic parameters in patients who have elevated blood pressure and non-insulin-dependent diabetes mellitus (NIDDM). After a 2-week run in placebo period, 20 NIDDM patients who had diastolic blood pressure in the range of 90 to 105 mm Hg underwent a randomized, single blind, placebo controlled, cross-over study of 4 week treatment with clonidine (transdermal patch 2.5 mg/week) or placebo (inactive patch). Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Our finding that clonidine treatment prevented the insulin resistance associated with weight gain in the dog is consistent with other reports. Giugliano et al 16 reported that in 20 hypertensive patients with non-insulin-dependent diabetes mellitus, clonidine treatment was associated with an improvement in insulin sensitivity in peripheral tissues. Using the glucose clamp, these investigators found that clonidine significantly improved overall glucose metabolism and that this improvement was accompanied by increases in both oxidative and nonoxidative glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that clonidine treatment prevented the insulin resistance associated with weight gain in the dog is consistent with other reports. Giugliano et al 16 reported that in 20 hypertensive patients with non-insulin-dependent diabetes mellitus, clonidine treatment was associated with an improvement in insulin sensitivity in peripheral tissues. Using the glucose clamp, these investigators found that clonidine significantly improved overall glucose metabolism and that this improvement was accompanied by increases in both oxidative and nonoxidative glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal clonidine has been successfully employed as adjunctive therapy with drug classes such as ACE inhibitors 16 and calcium channel blockers 17 ; however, when transdermal clonidine is provided as adjunctive therapy, it is unclear as to whether transdermal clonidine alone might have been sufficient for BP control 16 . Transdermal clonidine has also been shown to effectively reduce BP in hypertensive patients with type 2 diabetes while at the same time decreasing insulin resistance, microalbuminuria, and plasma fibrinogen 18 . In addition, clonidine (transdermal or oral) does not affect the cortisol response or the magnitude or rate of glucose recovery from insulin‐induced hypoglycemia 19 …”
Section: Blood Pressurementioning
confidence: 99%
“…96 A reflex increase in sympathetic tone in normotensive subjects can also lead to acute insulin resistance in the forearm. 97 Finally, clonidine, a drug that inhibits sympathetic outflow, improves insulin sensitivity in hypertensive patients with type 2 diabetes 98 and prevents insulin resistance in dogs fed a high-fat diet without affecting weight gain. 38 Whatever the mechanisms of insulin resistance, the cardiovascular consequences are serious: hyperinsulinemia and decreased vascular relaxation capabilities.…”
Section: Possible Mechanisms Of Obesity-induced Hypertensionmentioning
confidence: 99%